(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
This research evaluates the pedagogical efficacy of implementing structured storytelling activities to enhance the oral performance of intermediate B1 English as a Foreign Language learners. Utilizing a mixed-methods design, the study incorporates survey data gathered from twenty-one participants alongside an empirical classroom experiment. The initial diagnostic data highlights that major communicative barriers include lexical limitations, grammar errors, and psychological anxiety. To address these issues, an experimental group was exposed to a multi-stage narrative model incorporating cognitive mapping, word association drawings, visual prompts, and collaborative playacting. The experimental results reveal that over three-quarters of the students achieved heightened oral production when supported by teacher guidance and picture-based prompts. The study concludes that scaffolded storytelling activities significantly improve pronunciation, grammar utilization, and vocabulary recall. It provides concrete operational recommendations for curriculum developers to mitigate common institutional constraints such as limited materials and time management deficits.